2020
DOI: 10.1371/journal.pone.0230899
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome detection of sequence and structural polymorphism in six diverse horses

Abstract: The domesticated horse has played a unique role in human history, serving not just as a source of animal protein, but also as a catalyst for long-distance migration and military conquest. As a result, the horse developed unique physiological adaptations to meet the demands of both their climatic environment and their relationship with man. Completed in 2009, the first domesticated horse reference genome assembly (EquCab 2.0) produced most of the publicly available genetic variations annotations in this species… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Although detection methods for the former have been developed 11 – 16 , no methods are available for detecting genetic modifications. For this purpose, whole-genome sequencing 17 , which requires a detailed understanding of variations of the Thoroughbred genome, may be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Although detection methods for the former have been developed 11 – 16 , no methods are available for detecting genetic modifications. For this purpose, whole-genome sequencing 17 , which requires a detailed understanding of variations of the Thoroughbred genome, may be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies observed a similar trend on the same chromosomes for SNVs and nonsynonymous substitutions [ 7 , 16 ]. Although the exact reason for this is unknown, one reason is thought to be the existence of metabolic and sensory perception regions on chromosome 12, and immune response and antigen-processing regions on chromosome 20 [ 18 , 19 , 20 ]. These genes have several pseudogenes that lose their function because of substitutions, insertions, and deletions in the gene regions.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variants representing the population level polymorphisms were obtained from the following species and their available datasets: Equus caballus (EquCab2 assembly in the EVA study PRJEB9799 [81]), Bos taurus (UMD3.1 assembly in the NextGen project: https://projects.ensembl.org/nextgen/), Ovis aries (Oar v3.1 assembly in the NextGen project), Capra hircus (CHIR1 assembly in the NextGen project), converted to ARS1 assembly with dbSNP identifiers [82]), Chlorocebus sabaeus (ChlSab1.1 assembly in the EVA project PRJEB22989 [83]), Homo sapiens (GRCh38 assembly in the 1000 Genomes Project [84]). In total, we analyzed 28 populations across the 6 different species with polymorphism data.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic variants representing the population level polymorphisms were obtained from the following species and their available datasets: Equus caballus (EquCab2 assembly in the EVA study PRJEB9799 [81]),…”
Section: Polymorphism Datasetmentioning
confidence: 99%